2018
DOI: 10.3892/etm.2018.7056
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of skin lesions in contrast media-induced chemical hypersensitivity

Abstract: Contrast agents are used in radiology to increase the sensibility and specificity of radiological techniques. Some of these compounds have side effects that include organ toxicity (with kidney being the most affected organ) and hypersensitivity reactions. We performed multiple PubMed searches from January, 2008 to January, 2018 for studies regarding adverse reactions to compounds used as contrast agents in imagistic techniques. The initial research identified 929 records written in English. After further exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 56 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…Contrast-induced nephropathy (CIN) or contrast-induced acute kidney injury (CI-AKI) is an iatrogenic acute kidney injury (AKI) observed after intravascular administration of contrast media (CM) for diagnostic procedures or therapeutic angiographic interventions [ 1 4 ]. Chemical hypersensitivity has also been reported as another side effect of CM [ 5 ]. According to the Kidney Disease Improving Global Outcomes (KDIGO) clinical practice guidelines for AKI, a serum creatinine (Cr) increase of at least 0.3 mg/dL (or 26.5 µmol/L) over the baseline value within 48 h after exposure to CM, or an increase greater than 1.5 times over the baseline value within 7 days after exposure to CM, or a urinary volume of less than 0.5 mL/kg/h for at least 6 h after exposure, are the definition of this condition [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-induced nephropathy (CIN) or contrast-induced acute kidney injury (CI-AKI) is an iatrogenic acute kidney injury (AKI) observed after intravascular administration of contrast media (CM) for diagnostic procedures or therapeutic angiographic interventions [ 1 4 ]. Chemical hypersensitivity has also been reported as another side effect of CM [ 5 ]. According to the Kidney Disease Improving Global Outcomes (KDIGO) clinical practice guidelines for AKI, a serum creatinine (Cr) increase of at least 0.3 mg/dL (or 26.5 µmol/L) over the baseline value within 48 h after exposure to CM, or an increase greater than 1.5 times over the baseline value within 7 days after exposure to CM, or a urinary volume of less than 0.5 mL/kg/h for at least 6 h after exposure, are the definition of this condition [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extract of Indian gooseberry leaves demonstrated antioxidant and renoprotective effect in cisplatin-induced nephrotoxicity [8]. Moreover, contrast media-induced organ toxicity specially nephrotoxicity is one of the major concerns nowadays [6,9]. Again, natural products with antioxidant and free radical scavenging ability have the potential benefiacial effect in the prevention and treatment of organ toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In last two decades, various parameters of aminoglycoside-induced nephrotoxicity have been researched [21]. Reactive oxygen species (ROS) play the leading role in nephrotoxicity caused by the extensive accumulations of gentamycin in the kidney tissue [9,10,15]. Again, gentamycin increased intracellular calcium concentration causing mesengial cell contraction, in turn, can induce the renin-angiotensin system, resulting in the formation of many vasoconstrictor substances like angiotensin II, endothelin I, and thromboxane A 2 [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug reactions were reported by Iordache et al (20), which showed the incidence and different aspects of skin lesions in contrast-induced chemical hypersensitivity.…”
mentioning
confidence: 91%